INTEGRATING CLASSPOINT INTO PRESENTATION MEDIA FOR ENHANCING INTERACTIVE LINEAR ALGEBRA INSTRUCTION : Jakarta Timur, Makasar, Indonesia - Sovia, Anny; Tasni, Nurfaida; Murdiyanto, Tri; Haeruman, Leny Dhianti; Partasiwi, Nurashri; El-Hakim, Lukman (Jurnal Math-UMB.EDU, 2025)
The limited participation and motivation of students in conventional, lecturer-centered learning environments highlight the necessity for technological innovations that actively promote student engagement. This study aims to design and develop an interactive learning medium utilizing ClassPoint for the Linear Algebra course. The research adopted the ADDIE development model, encompassing the analysis, design, and development phases, and was limited to the validation stage. Two experts served as validators: one in content and the other in instructional media. Validation data were analyzed through quantitative descriptive techniques by calculating the mean percentage score and categorizing feasibility across four assessment aspects—content, presentation, language, and visual design. The validation results revealed that the ClassPoint-based learning media achieved a “highly valid” classification, with an average score exceeding 83%. These findings indicate that the developed media are suitable for classroom implementation and have strong potential to enhance students’ motivation and engagement through interactive features. Future research is recommended to evaluate the effectiveness of the media during the implementation stage, particularly concerning learning outcomes and the development of 21st-century skills.. Keywords: ClassPoint, interactive learning media, media validation, Linear Algebra, ADDIE model.